2006
DOI: 10.1021/jm0606387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Evaluation of M(I)(CO)3(NNO) Complexes (M = Re, 99mTc) Conjugated to 2-(4-Aminophenyl)benzothiazole as Potential Breast Cancer Radiopharmaceuticals

Abstract: The synthesis and biological evaluation of new M(I)(CO)3(NNO) (M = Re, 99mTc) complexes attached to the antitumor agent 2-(4-aminophenyl)benzothiazole are reported. The fluorescent rhenium complex enters MCF-7 breast cancer cells but does not enter normal HFFF-2 and MRC-5 cells. The analogous radioactive 99mTc complex produces fast blood and soft tissue clearance when administered to healthy mice. These complexes are promising candidates for developing radiopharmaceuticals for imaging (99mTc) and targeted radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 28 publications
1
67
0
2
Order By: Relevance
“…Compounds 3,6,8,10,11,12,16,18 and 20 were selected by NCI for 60 human tumor cell lines' anticancer screening test at single dose assay. In vitro single-dose anticancer assay was performed in full NCI 60 cell panel representing L, NSCLC, CC, CNSC, M, OC, RC, PC, and BC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 3,6,8,10,11,12,16,18 and 20 were selected by NCI for 60 human tumor cell lines' anticancer screening test at single dose assay. In vitro single-dose anticancer assay was performed in full NCI 60 cell panel representing L, NSCLC, CC, CNSC, M, OC, RC, PC, and BC.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, it was found that, 2-(4-aminophenyl)benzothiazole derivatives inhibit cancer cell growth with nanomolar scale against a large panel of human cancer cell lines particularly against breast, colon and ovarian cell lines in in vitro anticancer screening program of the National Cancer Institute (NCI) with a characteristic biphasic doseresponse relationship 6,7 . Up to present, scientists Shi and Bradshaw have a series of studies on antitumor activity of some benzothiazole derivatives [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Tzanopoulou et al, Figure 1 is a potential candidate for imaging techniques ( 99m Tc), facilitating breast cancer diagnosis [12,13]. In view of that, we have performed EPR calculations evaluating thermal and solvent effects on the hyperfine coupling constant (HFCC) in Complex 1.…”
Section: Thermal and Solvent Effects On The Hyperfine Coupling Constamentioning
confidence: 99%
“…More recently, radioisotopes of technetium (Tc) have been considered promising nuclei for the NMR (Nuclear Magnetic Resonance) and MRI techniques [9][10][11]. Based on this context, in 2006 Tzanopoulou et al synthesized the ( 99m Tc)(CO) 3 (NNO) complex conjugated to the antitumor agent 2-(4 -aminophenyl)benzothiazole [ABT; see Complex 1, Figure 1] [12]. The ABT compound presents nanomolar activity in vitro against some breast cancer cells in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The structural simplicity and synthetic accessibility of benzothiazole (1)(2)(3)(4) ,benzoxazole and benzimidazole series show remarkable antitumor properties. A series of potent and selective agents derived from 2-(4-Aminophenyl)benzothiazole structure was extensively examined and developed during recent years to have antitumor activity since 1996 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) , Unexpectedly, it was found that , 2-(4-aminophenyl) benzothiazole and related structure derivatives inhibit cancer cell growth with nanomolar scale against a large panel of human cancer cell lines particularly against breast , colon and ovarian cell lines in in-vitro anticancer screening program of the National Cancer Institute (NCI) with a characteristic biphasic dose-response relationship. The original (unsubstituted) member of this series, 2-(4-aminophenyl) benzothiazole was considered to be ''Lead ''approach to drug discovery of new anticancer agents.…”
mentioning
confidence: 99%